2019
DOI: 10.1101/717363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toxicity and bioaccumulation of Cadmium, Copper and Zinc in a direct comparison at equitoxic concentrations in common carp (Cyprinus carpio) juveniles

Abstract: AbstractThe individual toxicity and bioaccumulation of cadmium (Cd), copper (Cu) and zinc (Zn) towards common carp juveniles was evaluated in a direct comparison in two experimental setups. First, the fish were exposed for 10 days to different metal concentrations. Accumulated metals were quantified and showed a positive dose dependent uptake for cadmium and copper, but not for zinc. Toxicity was in the order Cd>Cu>Zn with 96h LC50 values (concentrati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…Although there are several studies describing the adverse effects of waterborne metals, it is 100 difficult to find information on the effects of metal mixtures. We chose a sublethal mixture of 101 Cu, Zn and Cd at a low concentrations (Cu: 0.08 µM; Cd: 0.03 µM and Zn: 3.16 µM) which 102 represent approximately 10% of the 96h LC 50 (the concentration that is lethal to 50% of the 103 population in 96h) earlier determined in our lab under the same exposure conditions (96h LC 50 104 Cu: 0.77 µM; Cd: 0.20 µM and Zn: 30 µM) (Delahaut et al, 2019a). An initial search of the 96h…”
supporting
confidence: 54%
“…Although there are several studies describing the adverse effects of waterborne metals, it is 100 difficult to find information on the effects of metal mixtures. We chose a sublethal mixture of 101 Cu, Zn and Cd at a low concentrations (Cu: 0.08 µM; Cd: 0.03 µM and Zn: 3.16 µM) which 102 represent approximately 10% of the 96h LC 50 (the concentration that is lethal to 50% of the 103 population in 96h) earlier determined in our lab under the same exposure conditions (96h LC 50 104 Cu: 0.77 µM; Cd: 0.20 µM and Zn: 30 µM) (Delahaut et al, 2019a). An initial search of the 96h…”
supporting
confidence: 54%
“…Moreover, we expect that metal accumulation would trigger defensive mechanisms, such as MT and GR to mitigate possible deleterious effects. Regarding ion-homeostasis, in agreement with previous results from our lab, we expect a Na but not a Ca loss (Castaldo et al 2020, Delahaut et al 2020 2. Material and methods…”
Section: Introductionsupporting
confidence: 92%
“…Two series of one-week waterborne exposures to binary mixtures of Cd and Cu were performed on common carp (length = 58.5 ± 6.8 mm; weight = 2.3 ± 0.9 g mean ± standard deviation (SD)). Besides control groups, treatments consisted of a fixed concentration of one of the metals at 25 % of the 96h-LC50 previously calculated in our lab (Delahaut et al 2020) combined with 10, 25 and 50 % of the 96h-LC50 of the other metal (indicated as Cufix/Cdvar or Cdfix/Cuvar). Exposure tanks consisting of five (plus one as backup in case of mortality) doublewalled polypropylene (PP) containers per treatment, each filled with 9 l of EPA medium-hard water and containing six fish, were set up in the climate chamber at 20°C.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Nanoparticles had been chosen to be involved in this study from the point of their rapidly growing concepts in tissue engineering for bone regeneration as mentioned by Mirzaei and Darroudi [ 34 ]. ZnONPs were selected because of their low toxicity, low cost and its availability compared to the other different natural non-organic metallic NPs [ 35 ], and Zn 2+ ions are well-known to stimulate bone formation and mineralization and to have an active role in the proliferation of osteoblastic cells [ 36 ]. Although the low toxicity of ZnONPs, their solubility may contribute to cytotoxicity, oxidative stress, and mitochondrial dysfunction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%